Unfolding COVID-19 vaccine communication campaigns in China’s neighborhoods: a qualitative study of stakeholders’ narratives - Yang, Ronghui; Han, Yanchao (Frontiers in Public Health, 2023)
Introduction: The Chinese state has recently implemented the COVID-19 Vaccine Communication Campaign (CVCC) to counter vaccine hesitancy. Nonetheless, the extant literature that examines COVID-19 vaccine acceptance has less represented COVID-19 vaccine communication efforts. Methods: To address this lacuna, we qualitatively explored how CVCCs were organised in Chinese communities by investigating 54 Chinese stakeholders. Results:This study indicates that the CVCC was sustained by top-down political pressure. CVCCs' components involve ideological education among politically affiliated health workers, expanding health worker networks, training health workers, implementing media promotion, communicating with residents using persuasive and explanatory techniques, encouraging multistakeholder partnerships, and using public opinion-steered and more or less coercive approaches. While CVCCs significantly enhanced COVID-19 vaccine acceptance, lacking open communication, stigmatising vaccine refusers, insufficient stakeholder collaboration and low trust in the COVID-19 Vaccination programme (CVP) eroded the validity of CVCCs. Discussion:To promote the continuity of CVCCs in China, CVCC performers are expected to conduct open and inclusive communication with residents. Furthermore, CVP planers should create robust partnerships among health workers by ensuring their agreements on strategies for implementing CVCCs and optimise COVID-19 immunisation service provision to depoliticise CVPs. Our study will not only deepen global audiences' understanding of CVCCs in authoritarian China, but also offer